A study by electrical conductivity measurements of the semiconductive and redox properties of Nb-doped NiO catalysts in correlation with the oxidative dehydrogenation of ethane1. Issue 12 (28th March 2015) - Popescu, Ionel; Skoufa, Zinovia; Heracleous, Eleni; Lemonidou, Angeliki; Marcu, Ioan-Cezar
<x xml:space="preserve">Abstract</x> All the catalysts were partially reduced during catalysis and the ODH selectivity was inversely correlated with their p-type semiconductivity under the reaction mixture.